KEPEMIMPINAN YANG MELAYANI DI SEKOLAH MENENGAH TINGKAT ATAS SWASTA KOTA SALATIGA - Handita Sari; Supramono Supramono (Kelola: Jurnal Manajemen Pendidikan, 2016)
This study aimed to describe the degree of servant leadership in Salatiga private high schools. This study used descriptive method in which the object of the research are three private schools in Salatiga. Data collection techniques used by spreading questionnaires to the three principals, teachers and employees at those shools and also with interview. Researched indicators arranged based on six characteristics of servant leadership: values people, develop people, build community, display authenticity, provide leadership, dan share leadership. The results of this study showed that the overall degree of servant leadership implementation in the  high category. However, there are some indicators that lead to the medium category. School principals are advised to be willing to improve some of these characteristics by first tried to listen to others. The results of this study can be used as a reference on servant leadership in secondary education.